2020
DOI: 10.3389/fimmu.2020.01195
|View full text |Cite
|
Sign up to set email alerts
|

Circulating microRNA Expression Profiling Identifies miR-125a-5p Promoting T Helper 1 Cells Response in the Pathogenesis of Hashimoto's Thyroiditis

Abstract: MicroRNAs (miRNAs) have emerged as key regulators of cellular processes by suppressing target mRNAs at the posttranscriptional level. However, little is known regarding the expression of miRNAs in peripheral blood mononuclear cells (PBMCs) from Hashimoto's thyroiditis (HT) patients. Therefore, 38 HT patients and 36 healthy volunteers were enrolled in this study to identify HT-mediated changes in miRNA expression. Over 1,000 dysregulated miRNAs and their biological functions in the HT patients were identified. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 49 publications
1
7
0
Order By: Relevance
“…Th1 cells are the predominant lymphocytes in the thyroid tissues from the HT patients which directly destroy thyroid follicular cells by activating cytotoxic lymphocytes and macrophages [7]. The previous studies have indicated that the proportion of peripheral Th1 cells was significantly increased in patients with HT [4,21]. Therefore, the factors contributing to Th1 cells in HT deserve further investigation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Th1 cells are the predominant lymphocytes in the thyroid tissues from the HT patients which directly destroy thyroid follicular cells by activating cytotoxic lymphocytes and macrophages [7]. The previous studies have indicated that the proportion of peripheral Th1 cells was significantly increased in patients with HT [4,21]. Therefore, the factors contributing to Th1 cells in HT deserve further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…It was first described in Japan by Dr. Hakaru Hashimoto over a century ago [2]. The clinical features of HT patients are characterized by increased thyroid volume, lymphocyte infiltration of interstitium between thyroid follicles, and the presence of specific antibodies to thyroid antigens, including antithyroglobulin antibody (TgAb) and antithyroperoxidase antibody (TPOAb) [3,4]. HT was long considered a rare disease until the change in diagnostic modality, mostly, the introduction of thyroid function and thyroid antibodies tests [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Human peripheral blood mononuclear cells (PBMCs) were isolated by density-gradient centrifugation over Ficoll-Hypaque solution (Haoyang Biological Technology Co., Tianjin, China) and stored at -80°C for quantitative real-time polymerase chain reaction (qRT–PCR). Human CD4 + T cells were isolated from PBMCs using human CD4 microbeads (Miltenyi Biotec GmbH, Bergisch Gladbach, Germany) as previously described ( 33 ). Human PBMCs and CD4 + T cells were cultured with RPMI-1640 medium (Gibco, California, USA) containing 10% foetal bovine serum (Gibco) for transfection.…”
Section: Methodsmentioning
confidence: 99%
“…cDNA reverse transcription and quantitative real-time PCR (qRT–PCR) were performed as previously described [ 18 ]. The primers are summarized in Supplemental Table S2 .…”
Section: Methodsmentioning
confidence: 99%